(3TQM GdeYdbGJ GdSHYs - (3dCHi LYaQ CMeO Hf eMeO Hf ESeGYjd GdeQGOi GdeUQjs; (3MSjf Hf CMeO Hf MSjf GdRhRfj, CHh YHO Gddg,J (B486 (3g` s ((3CMeO Hf eQhGf s)
(3ChdgG (B:s
(3cGf ef MOjK GdfGHZI , hGSeg RjGO hHf efYhjg Hf PHjGf , hHOA ZVH GdfYeGf cGfJ GdJeLQOI s
(3BNQgG (B:s
(3bGd dgG gd dc jGJGai bGdJ dg eG CfJ HGdeQVi BNQ GdeYdbGJ GdSHY hGdeVGaJjf EdjgG , TQM CHj GdLYaQ GdfMGS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGdKI jJab ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3HChdgG agQS ddeYdbGJ GdeTQhMg s
(3hHBNQ UaMGJgG JYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs